2021
DOI: 10.1177/1757743821989380
|View full text |Cite
|
Sign up to set email alerts
|

Teaching at Holocaust memorial sites: Swedish teachers’ understanding of the educational values of visiting Holocaust memorial sites

Abstract: The present article focuses on teaching and learning about the Holocaust in Sweden, conducted as study trips to Holocaust memorial sites. Although about a quarter of Swedish teenagers visit the Auschwitz-Birkenau State Museum each year, this study is the first to examine these Swedish study trips. Since there are no centralised systems for arranging these study trips, this study regards dedicated teachers as the main stakeholders. By deploying critical discourse analysis of transcripts of nine in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…As demonstrated in the results, there are also examples in this study where students link their interaction with historical artefacts at the site with cognitive reasoning in the present, including reflections on their place in a historical context. In this respect, the empirical analysis of the students' responses in this study contradicts previous research findings that suggest that affective experiences prevent effective learning (Flennegård and Mattsson, 2021). Zachrich et al's (2020) model has many merits.…”
Section: Conclusion and Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…As demonstrated in the results, there are also examples in this study where students link their interaction with historical artefacts at the site with cognitive reasoning in the present, including reflections on their place in a historical context. In this respect, the empirical analysis of the students' responses in this study contradicts previous research findings that suggest that affective experiences prevent effective learning (Flennegård and Mattsson, 2021). Zachrich et al's (2020) model has many merits.…”
Section: Conclusion and Discussioncontrasting
confidence: 93%
“…Extant research has indicated that Holocaust sites are complex places with different roles and functions that operate in tandem (Richardson, 2021). It has been suggested that the emotional experiences that accompany visits to such sites can hinder students' learning; however, the interplay between the cognitive, affective and physical dimensions of students' historical experiences in authentic learning contexts has not been explored fully yet (Flennegård and Mattsson, 2021;Nesfield, 2015). In research investigating visits to museums and historical sites, as well as the role that these sites play in teaching, questions about students' varying historical experiences are featured more prominently (see Marcus, 2007;Rohlf, 2015;Savenije et al, 2014;Spalding, 2011).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal learning settings such as visits to memorials, museums or events focusing on the Holocaust are generally highly valued by educators (Cohen, 2016; Flennegård & Mattsson, 2021; Oren & Shani, 2012; Oztig, 2023; Saba, 2012). In our study, we found a balance between formal and informal learning preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Study trips to Holocaust memorial sites, such as former concentration and extermination camps, have become increasingly important in creating high‐impact learning experiences (Flennegård & Mattsson, 2021; Saba, 2012). Holocaust museums and memorials play an important role in providing educational opportunities for teacher training, lifelong learning and raising awareness about education and remembrance (Oren & Shani, 2012; Oztig, 2023).…”
Section: Conceptual Framework and Related Literaturementioning
confidence: 99%